DINAMIKA ORANG PAPUA DALAM NIEUW GUINEA RAAD (NGR) 1961 DAN MAJELIS RAKYAT PAPUA(MRP) 2005 DI TANAH PAPUA - Bernarda Meteray (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2016)
One of the attempts to prevent Indonesia from disintegration is to avoid an inappropriate decision in the making of development policies. In the history of Papua, formation processes of the Nieuw Guinea Raad (NGR), 1961 and the Majelis Rakyat Papua (MRP), the Papuan People Council, 2005, in Papua have influenced the Indonesianess growing process among the Papuans. These two institutions have given a deeply significant meaning in the involvement of Papuans in an institution. Various approaches to improve the well-being of the Papuans have been implemented officially since 1969. Papua is, however, still considered the poorest region and is very often in conflicts. It was found that there has been something wrong with the development in Papua. Acemoglu and Robinson (2014) states that gaps between rich countries and poor ones are not merely due to cultural, geographical, and climatic factors, but they have been caused by political and economic institutions in the country itself as well. It has been these institutions having caused the country to come near the edge of failure. This paper is trying to show whether or not formation of the NGR and MRP had and have been suitable solutions to solve development problems and conflicts in Papua.